Mechanism of polysulfide immobilization on defective graphene sheets with N-substitution. (December 2016) - Rao, Dewei; Wang, Yunhui; Zhang, Lingyan; Yao, Shanshan; Qian, Xinye; Xi, Xiaoming; Xiao, Kesong; Deng, Kaiming; Shen, Xiangqian; Lu, Ruifeng
Abstract: The "shuttle effect" caused by the dissolution and diffusion of polysulfides in an electrolyte solution is the main factor that determines the performance decay for Li-S batteries. To overcome this problem, the electrode materials must be able to capture polysulfides. In this theoretical work, we explored the polysulfide fixation properties of N-substituted defective graphene by performing density functional theory calculations. From an analysis of the numerical results, including the structural configurations and charge redistribution of lithium-sulfides and the binding energies, charge density differences and density of Li2 Sn on graphene-based materials, we explained the mechanism of the dissolution and diffusion of Li2 Sn as well as its immobilization properties on N-substituted defective graphene.